Activation of the cGAS/STING axis in genome-damaged hematopoietic cells doesnNot impact blood cell formation or leukemogenesis - Dressel, Nicole; Natusch, Loreen; Munz, Clara M.; Costas Ramon, Santiago; Morcos, Mina; Loff, Anja; Hiller, Björn; Haase, Christa; Schulze, Livia; Müller, Patrick; Lesche, Mathias; Dahl, Andreas; et al. (Cancer research, 2023)
Genome damage is a main driver of malignant transformation, but it also induces aberrant inflammation via the cGAS/STING DNA-sensing pathway. Activation of cGAS/STING can trigger cell death and senescence, thereby potentially eliminating genome-damaged cells and preventing against malignant transformation. Here, we report that defective ribonucleotide excision repair (RER) in the hematopoietic system caused genome instability with concomitant activation of the cGAS/STING axis and compromised hematopoietic stem cell function, ultimately resulting in leukemogenesis. Additional inactivation of cGAS, STING, or type I IFN signaling, however, had no detectable effect on blood cell generation and leukemia development in RER-deficient hematopoietic cells. In wild-type mice, hematopoiesis under steady-state conditions and in response to genome damage was not affected by loss of cGAS. Together, these data challenge a role of the cGAS/STING pathway in protecting the hematopoietic system against DNA damage and leukemic transformation.Loss of cGAS/STING signaling does not impact DNA damage-driven leukemogenesis or alter steady-state, perturbed or malignant hematopoiesis, indicating that the cGAS/STING axis is not a crucial antioncogenic mechanism in the hematopoietic system.See related commentary by Zierhut, p. 2807
Gesehen am 02.11.2023